Pogodba o ureditvi premoženjskopravnih razmerij med zakoncema - Žnidaršič Skubic, Viktorija (Podjetje in delo, 2018)
The agreement on the regulation of property relations between spouses (marriage contract) is a novelty of Slovene family law, which was brought about by the adoption of the Family Code. In the paper, the author analyses some of the open questions that will undoubtedly appear upon introduction of the institute or upon use in practice. Initially, the author draws attention to the issue of the institution name, which, in her opinion, is inappropriate; therefore, in the article, the author uses the old and established term: marriage contract. The author continues with an analysis of the legal aspects of specific problems on the matter, such as questions regarding subjects of a marriage contract, the time aspect of concluding a contract and its effectiveness and the issue of its content. The author finishes the paper with the conclusion that introduction of autonomy into a sphere of property relations between spouses was necessary and should be welcomed as such, while also pointing out that the Pandora's box of difficulties in assessing the property relations between spouses has only really been opened.
Keywords: nesklenjena partnerska zveza; partnerska zveza; pogodbe; premoženje; premoženjska razmerja med zakoncema; premoženjski režim med zakoncema; zakonci; zakonska zveza; zunajzakonska skupnost; ženitna pogodba